The prognostic impact of variant allele frequency (VAF) in TP53 mutant patients with MDS: A systematic review and meta‐analysis. (27th July 2020) - Deng, Jili; Wu, Xia; Ling, Yantao; Liu, Xiaoyan; Zheng, Xue; Ye, Wu; Gong, Yuping
Abstract: Tumor protein p53 (TP53) is frequently expressed in patients with myelodysplastic syndromes (MDS). Studies have already reported the poor prognostic impact of TP53 gene mutations in MDS patients. However, parts of this subgroup of patients with low‐risk MDS still have relatively better survival and longer remission times. Therefore, we performed a meta‐analysis to evaluate the prognostic difference intra‐gene of variant allele frequency (VAF). The primary endpoint was overall survival (OS), and event‐free survival (EFS) was selected as the secondary endpoint. We extracted the hazard ratio (HR) and 95% confidence interval (CI) for OS and EFS from univariate and multivariate Cox proportional hazard models. A total of 4003 MDS patients and 1278 TP53‐mutated patients from 13 cohorts of 11 studies up to February 24, 2020, were included in our meta‐analysis. Pooled HRs suggested that a high mutant VAF had an adverse impact on OS (HR = 2.11, 95% CI: 1.48‐3.01, P  < .0001) but no impact on EFS (HR = 15.57, 95% CI: 0.75‐324.44, P  = .003) in MDS patients. Twenty percent is a proper threshold to set (HR = 2.02, 95% CI: 1.31‐3.13, P  = .001) and is a rough line between high clone burden and low clone burden, while 40% is an exact cutoff point (HR = 2.11, 95% CI: 1.26‐3.55, P  < .0001) to guide diagnosis and treatment. Beyond the traditional binary classification of gene mutation, we aimed to find a way to divide mutant molecular markers more specifically by VAF to provide clinical therapeutic values. Our meta‐analysis indicates that a high VAF is an independent, adverse prognostic factor for OS in TP53 mutant MDS patients. Patients with mediate/low‐frequency parts who could be treated like wide‐type patients have relatively better survival and may choose allogeneic hematopoietic stem cell transplantation as conditions permitting. Further prospective studies are needed in the future, and a large subgroup analysis of the same cutoff point subgroups is needed to obtain a more reliable basis for the impact of other mutant gene VAFs on the prognosis of MDS.